On the unconditional bases of cores generated by differential equations of the second order - Levchuk, V.N. (Reports of the National Academy of Sciences of Ukraine, 2017)
We obtain the necessary and sufficient conditions of unconditional basicity of functions that are solutions of second-order equations (Bessel-type), and the spectral parameter belongs to a discrete set coinciding with the zeros of an entire function of the exponential type.